(untitled) (The Pakistan Development Review, 2007)
Markets and government planning are providing alternative systems for coordinating people’s consumption of resources. The effectiveness of coordination depends on the capability of each system to signify accurate information about people’s wants and available supplies of resources. And on the incentives each provides for individuals to react to the desire of others [Hayek (1945) and Wills (2007)]. Natural resources generate public revenues and benefits. Its equitable distribution and sustainable production leads to real development and ultimately helped to poverty reduction and alleviation. Therefore, natural resource revenues necessitate distributions that favour the needs of the indigenous poor people and local sustainable development. Productive and high-value natural resources are seldom accessible to all citizens and their benefits are rarely evenly dispersed crosswise peoples and geographically across nations. It is worth mentioning that revenues collected from natural resources have a long history of being mismanaged and misappropriated—with political and economic elite often capturing a large share of the benefits while the nations disenfranchised must often absorb inexplicably large share of the associated social and environmental expenses. These are highly interdependence; a sound environment is crucial to poverty reduction and sustainable growth, particularly in low-income countries [IBRD/World Bank (2005); World Bank (2006a) and Mustafa (2008)].